The Expectations of Stakeholders in Socially Responsible Enterprises - Monika Jedynak; Aneta Kuźniarska (Journal of Emerging Trends in Marketing and Management, 2019)
The aim of the article is to determine what needs and expectations of stakeholders are indicated by socially responsible enterprises listed on the Warsaw Stock Exchange with the RESPECT Index (XII edition). The RESPECT Index is an income index addressing companies listed on the Warsaw Stock Exchange (hereinafter GPW), excluding the NewConnect market, foreign and dual-listed companies. The study population included 31 listed companies representing various sectors. Computer software, supporting the NVivo quality data analysis (version 12), was used to analyze documents as well as the content of reports and statements of the companies studied. The research conducted yielded results in the form of answers to the following questions that were posed: 1) Expectations of which stakeholders are identified in the enterprises surveyed? 2) What dimensions of CSR do the enterprises surveyed identify the expectations of stakeholders? 3) What tools were used to meet the expectations of stakeholders in the enterprises surveyed?